Análise de blocos de concreto com resíduo de borracha de pneu e metacaulim - Bravo, Rafael Segantini [UNESP] (2014)
Various segments of society have focused on the concepts of sustainability, researching alternatives to minimize the impacts caused by the often indiscriminate consumption of raw materials and the large volume of waste generated, among which include the waste rubber. Accordingly, many engineering studies have shown that the addition of waste rubber tire has the potential to promote the reduction of specific mass of cementitious matrices. Thus, the aim of this study was to evaluate the application of these wastes in the manufacture of lightweight concrete, with specific mass less than 2000 kg/m3, with a view to their application in concrete block masonry. It was observed that there was a decrease in compressive strength of the concrete, which is why we adopted the procedure of replacing 10% of metakaolin in cement (by mass). Still aim of this study, promote appropriate disposal for this waste and to minimize possible environmental impacts, often caused by their improper disposal. Ratio of concrete were produced without residue (reference concrete), with 9,2%, 18% and 26,8% of residue in substitution fine aggregate, in relative to the volume. Were produced cylindrical specimens 10 cm x 20 cm and concrete block 14 cm x 19 cm x 29 cm, which were tested in order to determine the compressive strenght. The concrete blocks were also tested for absorption. It was found that among the tested ratios, the less favorable result was obtained for the blocks produced with 26,8% of residue, which showed characteristic compressive strength of 2,74 MPa and absorption of 6,96%, results that meet the requirements of NBR 6136 for the manufacture of hollow concrete block mansory